Finance, growth and fragility: the role of government. (1st January 2013) - Beck, Thorsten
This paper offers a critical survey of the literature on the role of financial deepening in economic development, focusing on the role of government. Specifically, I distinguish between the policy view that relates financial sector development to an array of necessary policies and institutions, the historic view that relates financial sector development to historic and cultural factors, and the politics view that explains financial sector development as the result of political conflicts and decisions. These three views of financial sector deepening imply a different role for government. I discuss examples from the developed and developing world and repercussions for current reform discussions.